Childhood Sexual Abuse, Sexual Behavior, and Revictimization in Adolescence and Youth: A Mini Review - Castro, Ángel; Ibáñez, Javier; Maté, Berta; Esteban, Jessica; Barrada, Juan Ramón (Frontiers in Psychology, 2019)
Childhood sexual abuse (CSA) is considered as an activity aimed at providing sexual pleasure, stimulation, or sexual gratification to an adult who uses a minor for this purpose, taking advantage of the situation of superiority. CSA can have devastating consequences for the child. Previous studies have concluded that those who suffer an episode of CSA perform more risky sexual behaviors and are more likely to experience further episodes of sexual victimization during adolescence and early youth. There are two theoretical contributions that, although they offer partial views, can help to understand the association between CSA, sexual behavior, and revictimization in adulthood: the traumagenic dynamics model and the information-motivation-behavioral skills model. This short review provides an overview of the problems and theoretical explanations that have been presented up to the present, underlining the importance of prevention and sex education as of childhood, as well as the need to continue investigating in order to develop specific theoretical models that help to understand and prevent CSA and its consequences.